The challenges faced by female street vendors in Mbombela Municipality - Ngomane, T. S. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
With the advent of democracy after 1994, South African cities such as Johannesburg, Cape Town and Durban saw an influx of people looking for jobs. Due to scarcity of jobs many found themselves selling on street pavements. South Africa is argued to have a high rate of unemployment which is currently standing at 29%. Out of the population of 38.4 million people of working age, only 23 million are said to be employed. Street trading is said to be one of the areas that creates jobs for millions of people, especially women since they are in the majority about selling on the streets as compared to men. The aim of the study was to assess the challenges and constraints faced by female street vendors in Mbombela Local Municipality under Mpumalanga Province, and the responses made by various stakeholders including the vendors themselves. A qualitative research design was applied since the study was aimed at exploring and giving an in-depth analysis of the challenges faced by women as street vendors. Data was collected through semi-structured interview schedules from sixty (60) women who are street vendors from seven major markets in the Mbombela Municipality. Data was then summarised to capture emerging themes as well as opinions, attitudes and perceptions. The findings revealed that women trade on the street due to the high level of unemployment in the country. The results also revealed that street trading is supporting the economy of the country and neighbouring countries such as Mozambique and eSwatini by creating jobs for women. According to the results of the study, a majority of the female traders face challenges such as lack of storage for trading, waiting for long periods to get trading licences and lack of access to credit and training
Journal article published in The 5th Annual International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Business; Commodities; Economy; Infrastructure; Households; Street vendors; Unemployment; Street vendors